Implementation of the Bandung Command Center at the Bandung Polrestabes in Improving the Quality of Community Services - Rinto Dwi Hartomo, Jeremmy Theo Denoselli (Police Studies Review, 2024)
One of the technological innovations utilized by the Bandung Polrestabes is the application of the Bandung Command Center. The main function of the Bandung Command Center Application is a system that provides information on the occurrence of dangerous acts in a particular location. The importance of evaluating the implementation of the Bandung Panic Button Application in Bandung Police Polytechnic to optimize its use in public services. The purpose of this study is to analyze the implementation of the Bandung Command Center, analyze the factors that influence and explain the efforts to improve the quality of public services implemented by the Bandung Polrestabes through the Bandung Command Center. This research was conducted with a qualitative approach with field research methods carried out in the jurisdiction of the Bandung Regional Police of West Java Regional Police. Data collection techniques are done by observation, interview and document study. Data were analyzed with data validation and data triangulation techniques. The results of this study state that the implementation of the Bandung Command Center in Bandung Polrestabes is run in the form of online services through the Bandung Panic Button Application. Factors that hampered the implementation of the Bandung Panic Button Application stemmed from community reluctance as indicated by the uninstallation of the Bandung Panic Button Application on their mobile phones and the problem of lack of budgets for operations to be used in providing emergency services. Efforts to improve the quality of public services implemented by Bandung Polrestabes through the Bandung Command Center by collaborating with various stakeholders, fostering and supervising all personnel performance, implementing a reward and punishment system, making a budget plan for operational emergency services, providing a budget from Kapolrestabes assistance Bandung and coordinate integrated in the Bandung Command Center system.